Catalyst for hydrogen production through ammonia decomposition as well as preparation method and application of catalyst

By using highly graphitized carbon materials and alkali metal and rare earth metal oxide interfaces in the ammonia decomposition hydrogen production catalyst, the problems of high Ru dosage and limited reaction kinetics at low temperatures were solved, achieving ammonia decomposition hydrogen production with high activity at low temperatures and long-term stability.

CN120900625AActive Publication Date: 2025-11-07FOSHAN XIANHU LAB

Patent Information

Application Number
CN202511439812.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-10
Publication Date
2025-11-07
Estimated Expiration
2045-10-10

AI Technical Summary

Technical Problem

Existing ammonia decomposition hydrogen production catalysts suffer from excessive Ru content, limited low-temperature reaction kinetics, and insufficient NH3 conversion rates to meet industrial demands, necessitating further improvements in catalytic performance.

Method used

Using highly graphitized carbon material as a carrier, an interface is formed between alkali metal and rare earth metal oxides and Ru, optimizing the electronic structure of Ru active sites and enhancing the adsorption and activation capacity of ammonia. The thermal conductivity and chemical stability of highly graphitized carbon are then utilized to prepare a low-temperature, highly active, and long-lasting stable ammonia decomposition hydrogen production catalyst.

Benefits of technology

It achieves efficient hydrogen production from ammonia decomposition at low temperatures, with a conversion rate of 99.0-99.8% at 500℃. Its stability is superior to existing technologies, with a decay of less than 2% within 300 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120900625A_ABST
    Figure CN120900625A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and discloses an ammonia decomposition hydrogen production catalyst and a preparation method and application thereof. The preparation method of the catalyst for hydrogen production through ammonia decomposition comprises the following steps: in an inert atmosphere, successively carrying out calcination and acid treatment on a carbon carrier to prepare an acid-treated graphitized carbon carrier; adding a ruthenium precursor, a rare earth element precursor and an alkali metal precursor into ethanol, and mixing to prepare a mixed solution; then adding a graphitized carbon carrier into the mixed solution, and mixing; then adding urea and a surfactant, continuously mixing, and standing to obtain a solid precipitate; and finally, carrying out heat treatment on the solid precipitate in a reducing atmosphere. The catalyst takes a highly graphitized carbon material as a carrier, an alkali metal is doped to provide an alkaline environment, and a rare earth metal oxide and Ru form dual-assistant synergistic regulation of an interface, so that low-temperature high-activity ammonia decomposition hydrogen production and long-acting stable operation are realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of catalysts, and particularly relates to an ammonia decomposition hydrogen production catalyst and a preparation method and application thereof. BACKGROUND

[0002] Among the second energy carriers, hydrogen is considered an ideal choice due to its abundant source, high combustion heat value, and zero carbon emissions, and hydrogen energy has attracted high attention from scientific research institutions, enterprises, and other sectors. At present, the hydrogen-based sustainable energy industry is being promoted by society. However, storage and transportation are one of the key problems restricting its large-scale application. Ammonia is an ideal carrier for hydrogen storage and transportation. Ammonia has a high hydrogen content (17.6wt%), a large volume energy density, and is easy to liquefy at low pressure (the ammonia liquefaction temperature is -33℃ at normal pressure, while the hydrogen liquefaction temperature is -253℃), and compared with hydrogen, the storage and transportation containers of ammonia are smaller and lighter. Ammonia releases hydrogen through catalytic decomposition. The ammonia industry has a good safety record. About 150 million tons of ammonia are produced globally each year and transported to all parts of the world through existing sea, road, rail, and pipeline networks. Ammonia decomposition hydrogen production will greatly increase the scale of hydrogen energy market applications.

[0003] Catalysts can reduce the activation barrier of ammonia decomposition. Before the 1990s, Fe-based catalysts were widely used in ammonia decomposition research, but Fe catalysts had poor resistance to poisoning and were easily deactivated after high-temperature reaction. In the mid-1990s, Ru-based catalysts became the focus of research on catalytic decomposition of ammonia. J.C. Ganley et al. conducted experiments on 13 different metal catalysts, and the activity results showed that Ru > Ni > Rh > Co > Ir > Fe > Pt > Cr > Pd > Cu > Te, Se, Pb. Yin et al. studied the effects of active components Ru, Rh, Pt, Pd, Ni, Fe and different supports on the catalytic decomposition of ammonia to generate CO-free H2 x , and when CNTs were used as the carrier, the ammonia decomposition activity of the catalysts was in the order of Ru > Rh > Ni > Pt > Pd > Fe. Hendershot et al. studied the ammonia decomposition reaction of Ir, Ni, Cu, Pt, Ru, Pd and Rh on different carriers by FTIR method, and found that the ammonia decomposition catalytic activity was in the order of Ru > Ni > Ir > Pt > Fe. It can be seen that Ru is the most active among all pure elements, but its scarcity and high cost hinder its large-scale development, and its low-temperature conversion rate and stability also have certain development space. For example, Chinese invention patent CN 116139859 A discloses a Ru-based catalyst, the carrier of which is carbon-coated silicon dioxide SiO2@C, and the ammonia decomposition activity of the catalyst is 60000 mL / (h·g catThe conversion rate was 99.9% at 500℃, but the ammonia conversion efficiency was poor at low and medium temperatures, and the stability test only lasted 50 hours. Chinese invention patent CN 117983245 A discloses an ammonia decomposition hydrogen production catalyst and its preparation method, with a conversion rate of 99.9% at 500℃ and 30000 mL / (h·g) cat The conversion rate was 95% at the initial temperature, but the conversion rate was not high enough even though the temperature was not high. After 100 hours, the conversion rate decreased by 7%.

[0004] Therefore, research on ammonia decomposition hydrogen production catalysts is increasingly focused on improving catalytic performance while reducing the amount of precious metals used. Developing ammonia decomposition hydrogen production catalysts with low loading, high performance and high stability has become a key strategy for improving catalytic economics. Summary of the Invention

[0005] This invention addresses the common technical problems of ammonia decomposition hydrogen production catalysts, such as high Ru content, limited low-temperature reaction kinetics, and insufficient NH3 conversion rates to meet industrial demands under current economic temperatures. It proposes an ammonia decomposition hydrogen production catalyst, its preparation method, and its applications. This catalyst uses highly graphitized carbon material as a support. Through the synergistic regulation of a dual-promoter mechanism—alkaline environment provided by alkali metal doping and interface formation between rare earth metal oxides and Ru—the electronic structure of the Ru active sites is significantly optimized, enhancing the adsorption and activation capacity for NH3. Simultaneously, utilizing the excellent thermal conductivity and chemical stability of highly graphitized carbon, low-temperature, highly active ammonia decomposition hydrogen production and long-term stable operation are achieved.

[0006] To address the aforementioned technical problems, a first aspect of the present invention provides a method for preparing an ammonia decomposition hydrogen production catalyst, comprising the following steps: Acid-treated graphitized carbon support was prepared by calcining and acid treatment of the carbon support in an inert atmosphere. Ruthenium precursor, rare earth element precursor and alkali metal precursor are added to ethanol and mixed to prepare a mixed solution. The graphitized carbon support is added to the mixed solution and mixed; then urea and surfactant are added, and mixing continues. After standing, the solid precipitate is separated. The solid precipitate was heat-treated under a reducing atmosphere to obtain the ammonia decomposition hydrogen production catalyst.

[0007] Specifically, in the preparation process of the ammonia decomposition hydrogen production catalyst of the present application, the carbon carrier is first calcined at high temperature and treated with acid to obtain a graphitized carbon carrier with high specific surface area and excellent electron transfer capacity. Among them: the high specific surface area ensures the anchoring and dispersion of the carrier and the active site; high graphitization is conducive to improving the resistance to CH4 of the catalyst in the hydrogen-rich environment, thereby improving the stability of the catalyst. Then the ruthenium precursor, the rare earth element precursor, the alkali metal precursor and the graphitized carbon carrier are mixed and heat treated in a reducing atmosphere. Among them: the Ru ions in the Ru precursor form highly dispersed Ru nanoparticles in the reducing atmosphere due to the restriction of the graphitized carrier. At high temperature, the rare earth element precursor generates rare earth metal oxide, which is deposited near the Ru nanoparticles during the co-precipitation process and improves the coordination environment of the Ru surface, forming a Ru nanoparticle and rare earth metal oxide heterojunction. At the same time, the alkali metal precursor solution etches the surface of the carbon, causing significant changes in the surface of the carbon carrier; and during the heat treatment process, the alkali metal precursor and the graphitized carbon carrier undergo an alkali activation reaction to generate alkali metal, which is conducive to improving the overall alkalinity and alkaline sites of the material and forming an alkali metal single-atom doped carbon carrier.

[0008] In some embodiments of the present application, the temperature of the calcination is not less than 2000℃, and the time of the calcination is 2-4 hours.

[0009] Specifically, ultra-high temperature calcination above 2000℃ is conducive to improving the graphitization degree of the carbon carrier, thereby obtaining a graphitized carbon carrier with excellent electrical conductivity and chemical stability, laying a foundation for realizing low-temperature high-activity ammonia decomposition hydrogen production and long-term stable operation.

[0010] In some embodiments of the present application, the temperature of the calcination is 2000-3000℃, and the heating rate is 5-10℃ / min. Too low or too high calcination temperature is not conducive to the catalytic activity and stability of the graphitized carbon carrier.

[0011] In some embodiments of the present application, the intensity ratio ID / IG of the Raman D peak and G peak of the graphitized carbon carrier satisfies the relationship: 0.4≤ID / IG≤0.89.

[0012] Specifically, in the Raman spectrum analysis, the D peak and the G peak represent two characteristic peaks of the carbon material respectively. Among them: the D peak represents the structural defects or disorder in the carbon material, and the G peak represents the graphitization degree and structural order of the carbon material. The ID / IG ratio represents the intensity ratio of the D peak and the G peak, and the size is used to reflect the relative situation of the graphitization degree and the disorder degree in the carbon material. The larger the ratio is, the more structural defects or disorder in the material; on the contrary, the material has a higher graphitization degree and a lower disorder. The present application controls the ID / IG ratio range of the graphitized carbon carrier to ensure the graphitization degree of the carbon material.

[0013] In some embodiments of the present application, the acid treatment adopts a mixed solution of nitric acid and hydrogen peroxide.

[0014] In some embodiments of the present application, the concentration of the nitric acid is 65-75%, the concentration of the hydrogen peroxide is 25-35%, and the volume ratio of the nitric acid to the hydrogen peroxide is 1: (0.5-1.5).

[0015] In some embodiments of the present application, the inert atmosphere is a nitrogen or argon atmosphere, and the flow rate of the gas is 50-100 mL / min.

[0016] In some embodiments of the present application, the ruthenium precursor is selected from at least one of nitrosyl ruthenium nitrate and ruthenium chloride.

[0017] In some embodiments of the present application, the rare earth element precursor is selected from at least one of nitrate and hydrate of the rare earth element. For example, yttrium nitrate hexahydrate, lanthanum nitrate hexahydrate, praseodymium nitrate hexahydrate, cerium nitrate hexahydrate, etc.

[0018] In some embodiments of the present application, the alkali metal precursor is selected from at least one of nitrate and carbonate of the alkali metal. For example, potassium nitrate, potassium carbonate, etc.

[0019] In some embodiments of the present application, the mass ratio of the graphitized carbon carrier to the ruthenium precursor, the rare earth element precursor and the alkali metal precursor is 100: (1-10): (1-10): (1-10); and the preferred mass ratio is 100: (4-6): (4-6): (4-6).

[0020] In some embodiments of the present application, the surfactant includes cetyltrimethylammonium bromide (CTAB).

[0021] In some embodiments of the present application, the carbon carrier can use the commonly used carbon carrier in the art, i.e. XC-72, EC300J, ECP600JD, etc.

[0022] In some embodiments of the present application, the molar ratio of the urea to the ruthenium precursor is (15-30):1; and preferably, the molar ratio is (15-25):1.

[0023] In some embodiments of the present application, the mass ratio of the surfactant to the graphitized carbon carrier is (10-30):100; and preferably, the mass ratio is (10-20):100.

[0024] Specifically, urea has the characteristics of slow decomposition upon heating, and the surfactant (such as CTAB) has the adjusting effect on the ion concentration and local environment in the solution, so that the prepared composite precursor can be dissociated at a slower rate, thereby ensuring the mildness and uniformity of the precipitation.

[0025] In some embodiments of the present application, the temperature of the heat treatment is 450-800℃, and the time of the heat treatment is 1-3 hours.

[0026] In some embodiments of the present application, the heating rate of the heat treatment is 3-10℃ / min.

[0027] In some embodiments of the present application, the reducing atmosphere is a mixed atmosphere of hydrogen and argon, wherein the volume ratio of hydrogen is not less than 5%, and the flow rate of the gas is 50-200mL / min.

[0028] The second aspect of the present application provides an ammonia decomposition hydrogen production catalyst prepared by the above preparation method, which comprises a carrier and an active ingredient, the active ingredient is uniformly distributed on the surface of the carrier; the carrier is a single-atom alkali metal-doped graphitized carbon, the active ingredient comprises ruthenium metal nanoparticles and rare earth metal oxides, and the ruthenium metal nanoparticles and the rare earth metal oxides form a heterojunction interface.

[0029] Specifically, the ammonia decomposition hydrogen production catalyst of the present application significantly optimizes the mass transfer process by providing an alkaline environment through the alkali metal and the interface effect formed by the rare earth metal oxide and the ruthenium metal nanoparticles; at the same time, by improving the microstructure and surface properties of the catalyst, the diffusion and transport efficiency of ammonia, hydrogen and nitrogen are significantly improved, thereby accelerating the reaction rate and further improving the overall performance of the catalyst.

[0030] The third aspect of the present application provides the application of the above-mentioned ammonia decomposition hydrogen production catalyst in the ammonia decomposition hydrogen production reaction.

[0031] The conversion rate of the ammonia decomposition hydrogen production catalyst of the present application in the ammonia decomposition hydrogen production reaction can reach 99.0-99.8% when the reaction temperature is 500℃ and the space velocity is 30000mL / g / h.

[0032] The above technical solutions of the present application have at least the following technical effects or advantages compared with the prior art: (1) A good support should have strong conductivity to transfer electrons, and a high specific surface area to ensure anchoring and dispersion with active sites. This invention prepares a graphitized carbon support with high specific surface area and excellent electron transfer capability by subjecting the carbon support to ultra-high temperature calcination and acid treatment, which exhibits excellent performance in ammonia decomposition. Simultaneously, this invention further optimizes the performance of ammonia decomposition by alkali doping the graphitized support, providing sufficient electron density. Furthermore, a highly graphitized support can improve the catalyst's resistance to CH4 formation in a hydrogen-rich environment, thereby improving material stability. Therefore, the graphitized support of this invention significantly optimizes the mass transfer process of reactants and products by improving the catalyst's microstructure and surface properties, providing an important guarantee for efficient ammonia decomposition. Improving environmental alkalinity accelerates electron conduction, accelerating NH3 adsorption and N2 and H2 desorption processes, thereby accelerating the ammonia decomposition reaction and improving ammonia conversion performance.

[0033] (2) This invention mixes ruthenium precursor, rare earth element precursor, alkali metal precursor and graphitized carbon support, and performs heat treatment under a reducing atmosphere to bring Ru nanoparticles and rare earth metal oxides into close proximity. The rare earth metal oxides improve the coordination environment of the Ru surface, forming a heterogeneous interface between Ru nanoparticles and rare earth metal oxides. The interface effect not only accelerates mass transport and increases the reaction rate, thereby effectively enhancing the catalytic effect, but also affects the preferential orientation of Ru nanoparticles. The rare earth metal oxides, as an effective promoter to prevent high-temperature sintering of Ru nanoparticles, work together with Ru nanoparticles to enhance the structural stability of the catalyst, while reducing the deactivation of active sites and the occurrence of side reactions by optimizing surface properties and mass transfer processes.

[0034] (3) The ammonia decomposition hydrogen production catalyst prepared in this invention has good low-temperature high-efficiency catalytic activity and stability, achieving a space velocity of 30000 mL / hg at 500℃. -1 Under the given reaction conditions, the ammonia decomposition conversion rate can reach 99.0-99.8%; at a temperature of 773.15K, the decay rate is less than 2% after 300 hours. Attached Figure Description

[0035] Figure 1 This is a TEM image of the ammonia decomposition hydrogen production catalyst prepared in Example 1 of the present invention; Figure 2 The graph shows the ammonia decomposition conversion performance distribution of the ammonia decomposition hydrogen production catalysts prepared in Examples 1-4 and Comparative Examples 1-3 of this invention. Figure 3 This is a stability performance distribution diagram of the ammonia decomposition hydrogen production catalysts prepared in Example 1 and Comparative Example 1 of the present invention. Detailed Implementation

[0036] The present application will be described in detail below with reference to examples, so as to facilitate the understanding of the present application by those skilled in the art. It is necessary to point out here that the examples are only used to further illustrate the present application and cannot be understood as limiting the protection scope of the present application. Non-essential improvements and adjustments of the present application made by those skilled in the art according to the above description should still fall within the protection scope of the present application. Meanwhile, the raw materials mentioned below which are not described in detail are all commercially available products; the process steps or preparation methods which are not mentioned in detail are all known to those skilled in the art.

[0037] Example 1 A preparation method of an ammonia decomposition hydrogen production catalyst, comprising the following steps: (1) Put XC-72 carbon carrier into a high-temperature furnace, pass in 4 L / min argon, heat to 2000℃ at a rate of 10℃ / min, and keep for 3 h to prepare a graphitized carbon carrier with ID / IG of 0.89. Then mix 300 mL of the mixed solution with 10 g of the graphitized carbon carrier in a flask and connect a condenser reflux tube and a conical flask for recovering impurity gas products, heat to 80℃ and keep for 4 h, cool to room temperature, centrifuge and filter once (solid-liquid separation), then add deionized water, wash and suction filter, put into a vacuum oven, dry at 60℃ for 12 h, take out, grind in a mortar, and obtain the acid-treated graphitized XC-72 carbon carrier. The graphitized XC-72 carbon carrier is subjected to BET test, and the specific surface area is 956 m 2 / g.

[0038] (2) Add ruthenium nitrosyl nitrate, yttrium nitrate hexahydrate and potassium nitrate into ethanol, mix, prepare a mixed solution, and stir for 5 min; then add the graphitized XC-72 carbon carrier into the mixed solution, ultrasonic for 5 min and stir for 5 min; then add urea and CTAB, stir uniformly, and stand still; then filter the precipitate, wash with deionized water, and dry in an oven at 60℃; put the dried precipitate into a tube furnace under H2 / Ar (H2 volume ratio is 5%) atmosphere, heat to 800℃ at a rate of 3℃ / min, and keep for 2 h to prepare the K and Y2O3 dual-regulated Ru / C ammonia decomposition hydrogen production catalyst of the present example.

[0039] Wherein: the mass ratio of the graphitized XC-72 carbon carrier to ruthenium nitrosyl nitrate, yttrium nitrate hexahydrate and potassium nitrate is 100:5:5:5; the mass-volume ratio of the graphitized XC-72 carbon carrier to the mixed solution is 35 g:1 L; the molar ratio of urea to ruthenium nitrosyl nitrate is 20:1, and the mass ratio of CTAB to the graphitized XC-72 carbon carrier is 20:100.

[0040] Figure 1The image shows the TEM morphology of the ammonia decomposition hydrogen production catalyst prepared in this embodiment. Figure 1 The lattice fringes of Y₂O₃ and Ru can be clearly seen. Measurements show that the spacing between Y₂O₃ on the (222) crystal plane is 0.306 nm, and the spacing between Ru on the (101) crystal plane is 0.205 nm. Furthermore, the rare earth metal oxides Y₂O₃ and Ru form a clear heterogeneous interface. The formation of the heterogeneous interface is beneficial for accelerating product desorption and improving catalyst activity.

[0041] Example 2 A method for preparing an ammonia decomposition hydrogen production catalyst includes the following steps: (1) The acid-treated graphitized XC-72 carbon support was prepared using the same method as in Example 1.

[0042] (2) Add ruthenium nitrite, lanthanum nitrate hexahydrate and potassium nitrate to ethanol, mix to obtain a mixed solution, and stir for 5 min; then add graphitized XC-72 carbon support, sonicate for 5 min and stir for 5 min; then add urea and CTAB, stir evenly and let stand; then filter the precipitate, wash with deionized water, and dry in an oven at 60°C; place the dried precipitate in a tube furnace under an H2 / Ar (H2 volume percentage is 5%) atmosphere, heat to 800°C at a rate of 3°C / min, and keep at the temperature for 2 h to obtain the Ru / C ammonia decomposition hydrogen production catalyst with dual K and La2O3 regulation in this embodiment.

[0043] The mass ratio of graphitized XC-72 carbon support to nitrosyl ruthenium nitrate, lanthanum nitrate hexahydrate, and potassium nitrate is 100:5:5:5; the mass-volume ratio of graphitized XC-72 carbon support to the mixed solution is 35 g:1 L; the molar ratio of urea to nitrosyl ruthenium nitrate is 20:1; and the mass ratio of CTAB to graphitized XC-72 carbon support is 20:100.

[0044] Example 3 A method for preparing an ammonia decomposition hydrogen production catalyst includes the following steps: (1) Following the preparation method of Example 1, only the calcination temperature was changed to 3000℃, and the resulting graphitized carbon support ID / IG ratio was 0.4.

[0045] (2) Ru nitrosyl nitrate, praseodymium nitrate hexahydrate and potassium nitrate were added into ethanol, mixed to prepare a mixed solution, stirred for 5 min; then the graphitized XC-72 carbon carrier was added, ultrasonicated for 5 min and stirred for 5 min; then urea and CTAB were added, stirred uniformly, and left to stand; then the precipitate was filtered, washed with deionized water, and dried in an oven at 60℃; the dried precipitate was placed in a tube furnace under H2 / Ar (H2 volume ratio 5%) atmosphere, heated to 800℃ at a rate of 3℃ / min, and kept for 2 h to prepare K and Pr6O 11 Dual-regulated Ru / C ammonia decomposition hydrogen production catalyst.

[0046] The mass ratio of the graphitized XC-72 carbon carrier to Ru nitrosyl nitrate, praseodymium nitrate hexahydrate and potassium nitrate is 100:5:5:5; the mass-volume ratio of the graphitized XC-72 carbon carrier to the mixed solution is 35g:1L; the molar ratio of urea to Ru nitrosyl nitrate is 20:1, and the mass ratio of CTAB to the graphitized XC-72 carbon carrier is 20:100.

[0047] Example 4 A preparation method of an ammonia decomposition hydrogen production catalyst, comprising the following steps: (1) The acid-treated graphitized XC-72 carbon carrier was prepared by the same method as in Example 1.

[0048] (2) Ru nitrosyl nitrate, cerium nitrate hexahydrate and potassium nitrate were added into ethanol, mixed to prepare a mixed solution, stirred for 5 min; then the graphitized XC-72 carbon carrier was added, ultrasonicated for 5 min and stirred for 5 min; then urea and CTAB were added, stirred uniformly, and left to stand; then the precipitate was filtered, washed with deionized water, and dried in an oven at 60℃; the dried precipitate was placed in a tube furnace under H2 / Ar (H2 volume ratio 5%) atmosphere, heated to 800℃ at a rate of 3℃ / min, and kept for 2 h to prepare K and CeO2 dual-regulated Ru / C ammonia decomposition hydrogen production catalyst.

[0049] The mass ratio of the graphitized XC-72 carbon carrier to Ru nitrosyl nitrate, cerium nitrate hexahydrate and potassium nitrate is 100:5:5:5; the mass-volume ratio of the graphitized XC-72 carbon carrier to the mixed solution is 35g:1L; the molar ratio of urea to Ru nitrosyl nitrate is 20:1, and the mass ratio of CTAB to the graphitized XC-72 carbon carrier is 20:100.

[0050] Comparative Example 1 A preparation method of an ammonia decomposition hydrogen production catalyst, comprising the following steps: (1) The acid-treated graphitized XC-72 carbon carrier was prepared by the same method as in Example 1.

[0051] (2) The ruthenium nitrosyl nitrate was added into ethanol, mixed, and a ruthenium nitrosyl nitrate solution was prepared, and stirred for 5 min; then the graphitized XC-72 carbon carrier was added, ultrasonically treated for 5 min and stirred for 5 min; then the urea and CTAB were added, stirred uniformly, and left to stand; then the precipitate was filtered, washed with deionized water, and placed in an oven at 60°C for drying; the dried precipitate was placed in a tube furnace under H2 / Ar (H2volume ratio of 5%) atmosphere, and heated to 450°C at a rate of 3°C / min, and kept for 2 h, to prepare the Ru / C ammonia decomposition hydrogen production catalyst of the present comparative example.

[0052] The mass ratio of the graphitized XC-72 carbon carrier to the ruthenium nitrosyl nitrate was 100:5, and the mass-volume ratio of the graphitized XC-72 carbon carrier to the ruthenium nitrosyl nitrate solution was 35 g:1 L; the molar ratio of the urea to the ruthenium nitrosyl nitrate was 20:1, and the mass ratio of the CTAB to the graphitized XC-72 carbon carrier was 10:100.

[0053] The difference between Comparative Example 1 and Example 1 was that no yttrium nitrate hexahydrate and potassium nitrate were added in the preparation process.

[0054] Comparative Example 2 A method for preparing an ammonia decomposition hydrogen production catalyst, comprising the following steps: (1) The acid-treated graphitized XC-72 carbon carrier was prepared by the same method as in Example 1.

[0055] (2) The ruthenium nitrosyl nitrate and yttrium nitrate hexahydrate were added into ethanol, mixed, and a mixed solution was prepared, and stirred for 5 min; then the graphitized XC-72 carbon carrier was added, ultrasonically treated for 5 min and stirred for 5 min; then the urea and CTAB were added, stirred uniformly, and left to stand; then the precipitate was filtered, washed with deionized water, and placed in an oven at 60°C for drying; the dried precipitate was placed in a tube furnace under H2 / Ar (H2volume ratio of 5%) atmosphere, and heated to 600°C at a rate of 3°C / min, and kept for 2 h, to prepare the Y2O3-regulated Ru / C ammonia decomposition hydrogen production catalyst of the present comparative example.

[0056] The mass ratio of the graphitized XC-72 carbon carrier to the ruthenium nitrosyl nitrate and yttrium nitrate hexahydrate was 100:5:5; the mass-volume ratio of the graphitized XC-72 carbon carrier to the mixed solution was 35 g:1 L; the molar ratio of the urea to the ruthenium nitrosyl nitrate was 20:1, and the mass ratio of the CTAB to the graphitized XC-72 carbon carrier was 10:100.

[0057] The difference between Comparative Example 2 and Example 1 was that no potassium nitrate was added in the preparation process.

[0058] Comparative Example 3 A method for preparing an ammonia decomposition hydrogen production catalyst, comprising the following steps: (1) An acid-treated graphitized XC-72 carbon carrier is prepared by the same method as in Example 1.

[0059] (2) The ruthenium nitrosyl nitrate and potassium nitrate are added to ethanol, mixed to prepare a mixed solution, and stirred for 5 min; then the graphitized XC-72 carbon carrier is added, ultrasonically treated for 5 min and stirred for 5 min; then the urea and CTAB are added and stirred until uniform, and then left to stand; the precipitate is then filtered, washed with deionized water, and placed in an oven at 60°C to dry; the dried precipitate is placed in a tube furnace under a H2 / Ar (H2volume ratio of 5%) atmosphere, heated to 800°C at a rate of 3°C / min, and held for 2 h to prepare the K-regulated Ru / C ammonia decomposition hydrogen production catalyst of the present comparative example.

[0060] The mass ratio of the graphitized XC-72 carbon carrier to the ruthenium nitrosyl nitrate and potassium nitrate is 100:5:5; the mass / volume ratio of the graphitized XC-72 carbon carrier to the mixed solution is 35 g:1 L; the molar ratio of the urea to the ruthenium nitrosyl nitrate is 20:1, and the mass ratio of the CTAB to the graphitized XC-72 carbon carrier is 10:100.

[0061] The difference between Comparative Example 3 and Example 1 is that no yttrium nitrate hexahydrate is added during preparation.

[0062] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the calcination temperature of the XC-72 carbon carrier is 1000°C, and the graphitized carbon carrier prepared has an ID / IG of 0.98.

[0063] Comparative Example 5 A method for preparing an ammonia decomposition hydrogen production catalyst, comprising the following steps: (1) An acid-treated graphitized XC-72 carbon carrier is prepared by the same method as in Example 1.

[0064] (2) The ruthenium nitrosyl nitrate, yttrium nitrate hexahydrate, and potassium nitrate are added to ethanol, mixed to prepare a mixed solution, and stirred for 5 min; then the graphitized XC-72 carbon carrier is added, ultrasonically treated for 5 min and stirred for 5 min; then rotary evaporation is performed until the solvent is evaporated, at a temperature of 40°C and a rotation speed of 100 r / min; then the precipitate is placed in an oven at 60°C to dry. The dried precipitate is placed in a tube furnace under a H2 / Ar (H2volume ratio of 5%) atmosphere, heated to 450°C at a rate of 3°C / min, and held for 2 h to prepare the ammonia decomposition hydrogen production catalyst of the present comparative example.

[0065] The mass ratio of graphitized XC-72 carbon support to nitrosyl ruthenium nitrate, yttrium nitrate hexahydrate, and potassium nitrate is 100:5:5:5; the mass-volume ratio of graphitized XC-72 carbon support to the mixed solution is 35 g:1 L.

[0066] The only difference between Comparative Example 5 and Example 1 is that the solvent evaporation method is used instead of the coprecipitation method in Example 1.

[0067] Performance testing The ammonia decomposition hydrogen production catalysts prepared in Examples 1-4 and Comparative Examples 1-5 were tested for their ammonia decomposition reaction performance. The tests were conducted in a fixed-bed reaction system, where the reaction tube was a quartz tube with an inner diameter of 8 mm, and the catalyst loading was 0.1 g. The heat required for the reaction was provided by a vertical tube furnace. Pure NH3 was introduced at a rate of 50 mL / min within a temperature range of 300-550 °C to evaluate the catalytic performance. The temperature was maintained for 1 hour per test to ensure stability. The hydrogen emission concentration was analyzed online using a gas chromatograph equipped with a thermal conductivity detector. A stability test was conducted at 773.15 K for 300 hours, and the corresponding data were continuously collected.

[0068] The ammonia decomposition and conversion performance of Examples 1-4 and Comparative Examples 1-3 are as follows: Figure 2 As shown, by Figure 2 It can be seen that the dual-regulated catalysts prepared in Examples 1-4 exhibit significantly higher performance than the catalysts prepared in Comparative Examples 1-5. This indicates that the catalysts in Examples 1-4 demonstrate improved basicity sites and interfacial effects, promoting the desorption of hydrogen and nitrogen, thereby enhancing the catalyst activity. Specifically, the ammonia decomposition hydrogen production catalyst prepared in Example 1, at a relatively low temperature of 450°C, has a space velocity of 30000 mL / hg. -1 Under the given reaction conditions, the ammonia decomposition conversion rate can still reach 99.2%.

[0069] The stability performance of Example 1 and Comparative Example 1 is as follows: Figure 3 As shown, by Figure 3 It can be seen that the dual-regulated catalyst prepared in Example 1 has better stability than the catalyst prepared in Comparative Example 1, with a degradation of less than 2% after 300 h. The high stability is due to the synergistic effect of alkali metal and rare earth metal oxides, which not only enhances the structural stability of the catalyst, but also reduces the deactivation of active sites and the occurrence of side reactions by optimizing surface properties and mass transfer processes.

[0070] The ammonia decomposition hydrogen production catalysts prepared in Examples 1-4 and Comparative Examples 1-5 were tested at 500°C and a space velocity of 30000 mL / hg. -1 Under the reaction conditions, the ammonia decomposition conversion rate is shown in Table 1.

[0071] Table 1:

[0072] From Table 1, it can be seen that the ammonia decomposition hydrogen production catalysts prepared in Examples 1-4 all exhibit excellent ammonia decomposition performance under the conditions of a test space velocity of 30000 mL / g / h and a test temperature of 500℃, and the ammonia decomposition conversion rate can reach 99.0% or more, and even 99.8% in Example 1. Compared with Example 1, Comparative Examples 1-5 all result in different degrees of decline in ammonia decomposition conversion rate due to differences in the active components, carriers or preparation processes of the ammonia decomposition hydrogen production catalysts.

[0073] In summary, the use of different carbon-supported Ru and alkali metal and rare earth metal oxides in the catalyst has a significant positive enhancing effect on the performance of the catalyst. This synergistic effect is not only reflected in the performance improvement of the catalyst when each of them exists alone, but also in the significant performance gain when they work together. At the same time, the preparation process has a great influence on the catalytic performance of the catalyst.

[0074] For those skilled in the art to which the present application belongs, a number of simple deductions or substitutions can be made without departing from the concept of the present application, without having to undergo creative labor. Therefore, simple improvements made by those skilled in the art to the present application based on the disclosure of the present application should be within the scope of protection of the present application. The above examples are preferred embodiments of the present application, and any similar processes and equivalent changes made should be within the scope of protection of the present application.

Claims

1. A method for producing an ammonia decomposition hydrogen production catalyst, characterized by, The method comprises the following steps: The carbon carrier is calcined and acid treated successively under inert atmosphere to obtain an acid-treated graphitized carbon carrier; A ruthenium precursor, a rare earth element precursor and an alkali metal precursor are added into ethanol and mixed to obtain a mixed solution; The graphitized carbon carrier is added into the mixed solution and mixed, then urea and a surfactant are added and mixed, and the solid precipitate is separated after standing; The solid precipitate is heat treated under a reducing atmosphere to obtain the ammonia decomposition hydrogen production catalyst.

2. The method for producing an ammonia decomposition hydrogen production catalyst according to claim 1, characterized by, The calcination temperature is not less than 2000℃, and the calcination time is 2-4 hours.

3. The method for producing an ammonia decomposition hydrogen production catalyst according to claim 1 or 2, characterized by, The intensity ratio ID / IG of the Raman D peak and G peak of the graphitized carbon carrier satisfies the relationship 0.4≤ID / IG≤0.

89.

4. The method for producing an ammonia decomposition hydrogen production catalyst according to claim 1, characterized by, The acid treatment uses a mixed solution of nitric acid and hydrogen peroxide.

5. The method for producing an ammonia decomposition hydrogen production catalyst according to claim 1, characterized by, The ruthenium precursor is selected from at least one of ruthenium nitrosyl nitrate and ruthenium chloride; the rare earth element precursor is selected from at least one of a nitrate and a hydrate of a rare earth element; and the alkali metal precursor is selected from at least one of a nitrate and a carbonate of an alkali metal.

6. The method for producing an ammonia decomposition hydrogen production catalyst according to claim 5, characterized by, The mass ratio of the graphitized carbon carrier to the ruthenium precursor, the rare earth element precursor and the alkali metal precursor is 100:(1-10):(1-10):(1-10).

7. The method for producing an ammonia decomposition hydrogen production catalyst according to claim 6, characterized by, The molar ratio of the urea to the ruthenium precursor is (15-30):1, and the mass ratio of the surfactant to the graphitized carbon carrier is (10-20):

100.

8. The method for producing an ammonia decomposition hydrogen production catalyst according to claim 1, characterized by, The heat treatment temperature is 450-800℃, and the heat treatment time is 1-3 hours.

9. An ammonia decomposition hydrogen production catalyst characterized by, The ammonia decomposition hydrogen production catalyst prepared by the method of any one of claims 1-8 comprises a carrier and active ingredients, wherein the active ingredients are uniformly distributed on the surface of the carrier; the carrier is an alkali metal single atom-doped graphitized carbon, and the active ingredients comprise ruthenium metal nanoparticles and rare earth metal oxides, and the ruthenium metal nanoparticles and the rare earth metal oxides form a heterojunction interface.

10. The ammonia decomposition hydrogen production catalyst of claim 9 is applied in an ammonia decomposition hydrogen production reaction.

Citation Information

Patent Citations

  • Ru-based catalyst for hydrogen production through ammonia decomposition and preparation method of Ru-based catalyst

    CN116139859A

  • Catalyst for hydrogen production through ammonia decomposition, preparation method of catalyst and reactor for hydrogen production through ammonia decomposition

    CN117983245A

  • Application of metal-loaded catalyst taking rare earth carbonate as carrier precursor in ammonia decomposition reaction

    CN111215063A

  • Rare earth oxide post-supported ruthenium-based ammonia decomposition catalyst, preparation method and application thereof in preparation of hydrogen through ammonia decomposition

    CN120714626A

  • Ruthenium-based catalyst for hydrogen production from ammonia decomposition, preparation method therefor and application thereof

    US20200164346A1

Cited By

  • Platinum-iron catalyst, preparation method thereof, membrane electrode and fuel cell

    CN121307051A

  • A method for hydrogen production by ammonia alcohol co-decomposition

    CN122482401A